2014
DOI: 10.1007/s10535-013-0381-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plantain plantlets propagated in temporary immersion bioreactors and gelled medium during in vitro growth and acclimatization

Abstract: The current work compared the physiological characteristics of plantain (Musa AAB) plantlets micropropagated in temporary immersion bioreactors (TIB) and on a gelled medium (GM). The plantlets were evaluated during in vitro growth (in the shoot elongation phase) and at the end of ex vitro acclimatization. TIB improved rooting and gave rise to longer shoots and higher dry mass. Respiration rate was the highest at the beginning of shoot elongation in both the TIB and GM plantlets. Photosynthetic rate in TIB was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 45 publications
3
22
0
3
Order By: Relevance
“…The advantage of SABs is that they increase multiplication rates, allow greater availability of culture medium components and reduce production costs [ 7 , 8 , 9 ]. Micropropagation in SABs promotes photosynthesis and respiration, both caused by an increase in chlorophyll synthesis and stomatal functionality [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of SABs is that they increase multiplication rates, allow greater availability of culture medium components and reduce production costs [ 7 , 8 , 9 ]. Micropropagation in SABs promotes photosynthesis and respiration, both caused by an increase in chlorophyll synthesis and stomatal functionality [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…plants from TIB cultures had a higher survival rate than those from gelled medium. Photosynthetic rate at the midpoint of acclimatized plants grown in TIB cultures was significantly higher than that of plants grown in gelled media (Aragon et al 2014). Chlorophyll content of leaves is indirectly related to nitrogen content, and carotenoids increase antioxidant activity with leaf growth (Zhao et al 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Many previous reports indicated that plantlets from TIS had greater growth, with rapid adaptation after exposure to ex vitro conditions than SSS and CIS derived plant [18,33]. This might be because TIS enhanced stomatal functioning and improved photosynthesis and transpiration [31,34]. However, E. flava plantlets visibly wilted during transfer to ex vitro acclimatization.…”
Section: Discussionmentioning
confidence: 99%